Risk management awareness at Bako National Park / Nuraini Putit …[et al.] - Putit, Nuraini; Chan, Margaret Kit Yok; Hanan, Hanif (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2014)
People travel to national parks to experience, anticipating a degree of adventure which ironically, the grandeur nature that attracts people to natural areas may also put them at risk. In Sarawak, there was no provision to evaluate the tour guides’ awareness in risk management in the national parks and nature reserves before the implementation of licensing park guiding in 2007. This paper investigates the awareness of risk management among the candidates attending the training course in Bako National Park and their comprehension of their responsibilities during the practical examination conducted in relation to their experience in guiding. This study identifies strategic communication and demonstrative strategies employed, extends audiencecentered communication to include both informal messages and demonstrative practices through observational data. The study revealed that before the Certificate in Park Guide training course was introduced in 2007, there were higher number of incidents that required emergency attention and accidents in Bako National Park. Since then, the number of emergency incidents and accidents had shown a decreasing trend.